Bisphosphonate Functionalized Gadolinium Oxide Nanoparticles Allow Long‐Term MRI/CT Multimodal Imaging of Calcium Phosphate Bone Cement. Issue 19 (17th August 2018) - Mastrogiacomo, Simone; Kownacka, Alicja E.; Dou, Weiqiang; Burke, Benjamin P.; de Rosales, Rafael T. M.; Heerschap, Arend; Jansen, John A.; Archibald, Stephen J.; Walboomers, X. Frank
Abstract: Direct in vivo monitoring of bioconstructs using noninvasive imaging modalities such as magnetic resonance imaging (MRI) or computed tomography (CT) is not possible for many materials. Calcium phosphate–based composites (CPCs) that are applicable to bone regeneration are an example where the materials have poor MRI and CT contrast; hence, they are challenging to detect in vivo. In this study, a CPC construct is designed with gadolinium‐oxide nanoparticles incorporated to act as an MRI/CT multimodal contrast agent. The gadolinium(III) oxide nanoparticles are synthesized via the polyol method and surface functionalized with a bisphosphonate (BP) derivative to give a construct (gadolinium‐based contrast agents (GBCAs)‐BP) with strong affinity toward calcium phosphate. The CPC‐GBCAs‐BP functional material is longitudinally monitored after in vivo implantation in a condyle defect rat model. The synthetic method developed produces nanoparticles that are stable in aqueous solution (hydrodynamic diameter 70 nm) with significant T 1 and T 2 relaxivity demonstrated in both clinical 3 T and preclinical 11.7 T MRI systems. The combination of GBCAs‐BP nanoparticles with CPC gives an injectable material with handling properties that are suitable for clinical applications. The BP functionalization prolongs the residence of the contrast agent within the CPC to allow long‐term follow‐up imaging studies. The useful contrast agent properties combined with biological compatibility indicate further investigation of the novel bone substitute hybrid material toward clinical application. Abstract : Noninvasive in vivo imaging of bioconstructs to monitor hard tissues regeneration is currently a challenge. Calcium phosphate cements (CPCs) supplemented with a gadolinium‐based contrast agent (GBCAs) allow multimodal longitudinal imaging of the construct by magnetic resonance imaging and computed tomography. Surface functionalization of GBCA with bisphosphonate derivative enhances affinity toward CPC and the biological compatibility.